2014
DOI: 10.1016/j.nicl.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

48 echo T2 myelin imaging of white matter in first-episode schizophrenia: Evidence for aberrant myelination

Abstract: Myelin water imaging provides a novel strategy to assess myelin integrity and corresponding clinical relationships in psychosis, of particular relevance in frontal white matter regions. In the current study, T2 myelin water imaging was used to assess the myelin water fraction (MWF) signal from frontal areas in a sample of 58 individuals experiencing first-episode psychosis (FEP) and 44 healthy volunteers. No differences in frontal MWF were observed between FEP subjects and healthy volunteers; however, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
2
37
2
Order By: Relevance
“…The results suggest that across examined regions, peak myelin content is found around the fourth-sixth decade of life. The observed positive linear association between age and MWF up to the middle age is in agreement with the reports on samples that included only that part of the adult life span (Flynn et al, 2003; Lang et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results suggest that across examined regions, peak myelin content is found around the fourth-sixth decade of life. The observed positive linear association between age and MWF up to the middle age is in agreement with the reports on samples that included only that part of the adult life span (Flynn et al, 2003; Lang et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…Notably, diffusion-based indices in the same sample evidences curvilinear relationship with age in some regions (Billiet et al, 2015). In two other studies that used multi-echo T2 imaging sequences but were not designed to examine age differences, linear increase in MWF with age was observed (Flynn et al, 2003; Lang et al, 2014). Notably, in these two studies, sample age covered the range from early or late childhood to the middle age: 15–55 years (Flynn et al, 2003) and 5–40 (Lang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, small participant numbers were used and the authors acknowledged that the patients' use of antipsychotic medication could have altered activity in the globus pallidus, likely accounting for the changes observed (Spaniel et al, 2005). Another study found no difference in the MWF in the frontal white matter during the early stages of schizophrenia (Lang et al, 2014).…”
Section: Imaging Myelin In Neuropathology and Psychiatric Disordersmentioning
confidence: 99%
“…Myelin water fraction (MWF), defined as the fraction of the total signal which has T 2 < 40 milliseconds at 3 Tesla, has been histologically validated as a marker of myelin density in human tissue, 30–32 and has good scan‐rescan reproducibility (coefficient of variation 4% in cerebral white matter) 33 . MWI has been used to investigate myelin in a wide range of diseases including multiple sclerosis, neuromyelitis optica spectrum disorder, schizophrenia, Niemann‐Pick disease, prenatal alcohol exposure, amyotrophic and primary lateral sclerosis, Krabbe disease, autism, stroke, and traumatic brain injury 34–47 . Rapid myelination has been demonstrated in early childhood and adolescence using multicomponent driven equilibrium single pulse observation of T 1 and T 2 (mcDESPOT), an alternate approach to MWI using a steady‐state acquisition 48–53 .…”
Section: Introductionmentioning
confidence: 99%